Ignition and combustion behavior of gel fuel particles with metal and non-metal additives - Glushkov, Dmitrii O.; Paushkina, K. K.; Pleshko, A. O.; Yanovsky, Vyacheslav A. (Acta astronautica)
A group of elastically deformable gel fuel compositions was prepared from oil-filled cryogels with fine particles (Al, Cu, Fe, carbonaceous, inert) and without them. Fuel particles exposed to radiant heating at an oxidizer temperature of 600–1000 °C consistently ignited with dispersion that had a positive effect on the intensity of the fuel component burnout. For different fuel compositions, the ignition delay times vary from 1 to 10 s, the velocities vary from 0.3 to 1.4 m/s, and the average diameters of the burnout area vary from 7 to 15 mm. At heated air temperatures above 900 °C, the ignition delay times are quite similar. Within the whole range of source temperatures, the fuel composition with fine carbonaceous particles ignites most rapidly. The gel fuel composition with Al particles is characterized by the highest ignition delay times and lowest velocities of fine fragments.